Research on social identity effects of left-right hand coordination training in morin Khuur beginners from a group dynamics perspective - BAISARINA; Bayarmaa Gombo (Environment and Social Psychology, 2025)
Based on group dynamics theory, this study employed a quasi-experimental design to explore the social identity effects and underlying mechanisms in left-right hand coordination training for novice Morin Khuur learners. Through a 12-week controlled experiment involving 80 Morin Khuur beginners, participants were randomly assigned to either a group training environment (experimental group, n=40) or an individual training environment (control group, n=40). Statistical methods including repeated measures ANOVA, mediation analysis, and moderation analysis were systematically employed to examine the impact of group environment on left-right hand coordination development and the mediating role of social identity. The results revealed: (1) The group training environment significantly outperformed the individual training environment, with the experimental group achieving an overall coordination improvement of 121.3% and an effect size of 1.35; (2) Social identity played a crucial mediating role between group environment and coordination development, with the mediation effect accounting for 68.5% of the total effect, among which group belonging contributed the most (45.9%); (3) Group cohesion significantly moderated the social identity effect, with high-cohesion groups demonstrating a mediation effect of 73.2%, substantially exceeding the 58.4% observed in low-cohesion groups; (4) Cultural identity significantly moderated group training effectiveness, with the high cultural identity group showing a mediation effect of 76.8%, and Mongolian students exhibiting the strongest cultural identity moderation effect; (5) Peer support networks influenced learning outcomes through a triple mechanism of emotional support, instrumental support, and informational support, with the high support network group achieving coordination improvement of 149.4%. This study validates the applicability of social identity theory in traditional music skill learning, provides scientific evidence for group-based music teaching models, and holds significant theoretical value and practical implications for promoting traditional cultural transmission and music education innovation.